2015
DOI: 10.1080/03630242.2015.1074636
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of body image dissatisfaction in postmenopausal women

Abstract: Dissatisfaction with one's body image is widespread and can have serious health consequences; however, research about its prevalence and correlates in older women is limited. We analyzed data from 75,256 women participating in the Women's Health Initiative Observational Study, a longitudinal study of postmenopausal women's health. Measures used in the study were collected at baseline and/or the third year of follow-up between 1993 and 2002. The majority of participants (83%) in this study were dissatisfied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
3
18
1
Order By: Relevance
“…In the present study, higher DWL were related to lower levels of physical activity, which was consistent with existing literature [ 24 , 45 , 46 , 47 , 48 , 49 , 50 ]. High weight perception has been associated with lower levels of physical activity in adults [ 51 ], however current results are controversial and no definite conclusion can be drawn in this regard [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, higher DWL were related to lower levels of physical activity, which was consistent with existing literature [ 24 , 45 , 46 , 47 , 48 , 49 , 50 ]. High weight perception has been associated with lower levels of physical activity in adults [ 51 ], however current results are controversial and no definite conclusion can be drawn in this regard [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, in the 2 to 4 years leading up to menopause, women experience weight gain and a redistribution of body fat to the abdominal depot [1,4]. Women also report greater body image dissatisfaction [17], which may be related to the desire for weight loss or weight maintenance. Additionally, increased body weight — specifically subcutaneous adipose tissue — is associated with more adverse health conditions and more severe VMS during the menopause transition [18].…”
Section: Discussionmentioning
confidence: 99%
“…The Pilates method has often been shown to be effective in the increased release of serotonin from the brain. Increased levels of serotonin can be helpful in the reduction of the symptoms associated with depressive symptoms and poor or pessimistic attitudes (Ginsberg et al, 2016;Hassan & Amin, 2011). Further, breathing as an integral aspect of Pilates has been found to have a positive effect on the vagus nerve, which can influence emotional states such as anxiety and depression (Frank, Edwards, & Larimore, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The control of large group muscles with coordination, and focusing on breathing may increase aerobic capacity (Caldwell, Harrison, Adams, & Triplett, 2009), and further improve mental health (Kucuk & Livanelioglu, 2015). Heretofore, some researchers have also reported that the holistic approach of Pilates based training may offer physical and psychological improvements for human health (Akbas & Erdem, 2016;Bernardo, 2007;Cruz-Ferreira et al, 2011;Karaman, Yuksel, Kinikli, & Caglar, 2017;Kucuk & Livanelioglu, 2015), and various intensities benefit quality of life, mental health, fatigue, physical fitness levels, and body types in diverse rates (Anderson & Spector, 2000;Arslan, Çakmakçi, Taşkin, Çakmakçi, & Ismet, 2012;Ashrafinia et al, 2015;Caldwell et al, 2009;Campos de Oliveira, Gonçalves de Oliveira, & Pires-Oliveira, 2015;Cruz-Ferreira et al, 2011;Frank, Edwards, & Larimore, 2017;Ginsberg et al, 2016;Hassan & Amin, 2011;Kucuk & Livanelioglu, 2015;Leopoldino et al, 2013;McGrath, O'Malley, & Hendrix, 2011;Memmedova, 2015;Miller & Mesa, 2013;Pourvaghar, Bahram, Sharif, & Sayyah, 2014;Rogers & Gibson, 2009;Roh, 2016;Segal, Hein, & Basford, 2004;Shanazari, Marandi, & Minasian, 2013;Soysal Tomruk, Uz, Kara, & Idiman, 2016;Stan et al, 2012;Şavkın, 2014;Vieira, Faria, Wittmann, Teixeira, & Nogueira, 2013). The method is recommended by health professionals, both as rehabilitative for the people who have diseases, and preventive for undiagnosed or healthy individuals…”
Section: Introductionmentioning
confidence: 99%